Recognizing the riches of the forest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Non-wood products from forests represent an important, though underestimated, part of the economy of many developing countries. For hundreds of millions of people forests are a vital source of food, medicine, raw materials and income, and for...